Anti -dumping or protection: an analysis of competition issues in dumping investigations - Mastara, Shupikile (Department of Commercial Law, 2016)
'J. Michael Finger once portrayed the anti-dumping regime as a "witches' brew of the worst of policy making: power politics, bad economics, and shameful public administration.'' The thesis looks at the role of competition in anti-dumping investigations. With the growth in the initiation of anti-dumping investigations, there is concern that the limitations in the anti-dumping regulation open the system up to abuse. Article VI of the General Agreement on Tariffs and Trade (GATT) 1994 describes dumping as the act of selling goods in an export market at a lower price than the country of origin. This act is comparable to that of price discrimination or predation in competition law. However, the imprecise definition of key terms in anti-dumping law such as 'normal value', and 'material injury' permits industries to take advantage of these loopholes to gain protection from foreign competitors. This challenge has been reflected in the South African poultry industry where anti-dumping measures have been used as a way of protecting the market. This is reflected in the comment from ITAC who stated that it was important to 'give consideration to a country being able to produce a strategic protein source but at affordable prices… [And] A balance between the viability of domestic producers of a strategic industry with the affordability of food for the lower income group is critical for food security.' Recommendations have been put forward to deal with the limitations in the anti-dumping regulation with some calling for the removal of the anti-dumping legislation to be replaced with an international competition network. However the political nature of anti-dumping suggests that the best way to safeguard competition in dumping investigations is to incorporate competition principles in anti-dumping regulation. These include redefining key terms which are ambiguous, as well as increased cooperation between the trade and competition regulators to ensure the promotion of trade and competition.